Exploring New Depths: How Could Passengers Interact with Future In-Car Holographic 3D Displays? - Kazhura, Maryia (HCI in Mobility, Transport, and Automotive Systems, 2022)
Holographic 3D (H3D) displays have the potential to enhance future car interiors and provide users with a new dimension of visual and interactive experience, offering a larger depth range than other state of the art 3D display technologies. In this work, a user-elicited gesture set for 3D interaction with non-driving related tasks was built and evaluated. As the H3D technology itself is still in development, mixed reality headsets (Hololens 1 and 2) were used to emulate a virtual H3D display. In a gesture-elicitation study, N = 20 participants proposed mid-air gestures for a set of 33 tasks (referents) displayed either within or outside of participants’ reach. The resulting set of most mentioned proposals was refined with a reverse-matching task, in which N = 21 participants matched referents to videos of elicited gestures. In a third evaluation step, usability and memorability characteristics of the user-elicited gesture set were compared to those of an expert-elicited alternative using a between-subjects design with N = 16 participants in each group. Results showed that while both sets can be learned and recalled comparably well, the user-elicited gesture set was associated with a higher gesture suitability and ease, a higher perceived intuitiveness and a lower perceived mental effort. Implications for future H3D in-car interfaces are discussed.